Competitive Intelligence and the Sales Force - Le Bon, Jöel (Business Expert Press, 2014)
Ebook from IG Library ; Government intelligence agencies throughout the world are finding once again that human abilities and sources rather than technology are more reliable and instrumental in intelligence gathering efforts. Companies have known this for quite some time and have tried to leverage their best source of competitive intelligence: the sale force!